Fashion-Hub Di Batam Dengan Pendektan Arsitektur Ekspresionisme - Finia, Myisha Amanda; Firzal, Yohannes; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fashion-Hub in Batam is a center for fashion activities that centrally functioned as a space for interaction in educational, information, commercial and recreational activities for the society and can bridge the activities regarding the fashion world in local and international circles. By using an expressionism architecture approach, building can express an emotion expressed by the architect and can be felt by people who see it, able to display the image of fashion art itself, resulting in buildings that look like a work of art. Through a concept that is fashionable, this building has space quality for observers to simply admire its beauty, so that fashionable can be seen not only through cloths, bags and accessories, but also fashionable values itself can be seen through architectural buildings.Keywords: Batam, Expressionism Architecture, Fashion-Hub, Fashionable, Fashion World,